Perhitungan Jasa Pelayanan Dengan Metode Proporsi Konversi di Rumah Sakit Umum Daerah Sijunjung - Rahmawati Rahmawati; Delfia Tanjung Sari (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
The transformation of Indonesia's healthcare system is being accelerated through the National Health Insurance (JKN) Program, with coverage reaching 98.45% by 2024. The shift in payment mechanisms from fee-for-service (FFS) to Indonesian Case-Based Groups (INA-CBGs) package rates poses challenges for regional public hospitals (RSUD) with BLUD status, particularly in the fair and performance-based distribution of services. This study aims to evaluate the service distribution formula in effect at Sijunjung Regional Hospital and formulate a system based on the proportion conversion method, which converts INA-CBG claims into unit rates per service type by considering unit contributions, individual roles, and performance. The study used secondary data from January 2025 with total sampling, including data on revenue, service distribution, service decrees, performance assessments, and service formularies. The analysis shows that the existing formula has weaknesses, including an imbalance of medical and paramedical services of up to 13%, a disproportionate distribution of supporting services, a division of nurses that does not reflect workload, a uniform room index despite different patient numbers, and weak distribution rules at the room level. The study recommends a proportion-conversion formula based on the principles of no work, no pay; propriety; equality; and proportionality to increase human resource motivation, support the performance of regional general hospitals, and maintain service quality in the JKN era.